Optimalisasi Kinerja Bellboy Menuju Service Excellence di Grand Puri Saron Hotel - Rafael Ananda Aldy Mahendra; Tuwuh Adhistyo Wijoyo (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the optimization of the bellboy’s role in implementing Standard Operating Procedures (SOP), identify service gaps in the field, and evaluate motivational factors to enhance service excellence and customer satisfaction. Using a descriptive qualitative approach, this research was conducted at the Grand Puri Saron Hotel, Yogyakarta, from March to May 2026. Data were collected thru direct observation, documentation study, and in-depth interviews with the management. The research results indicate that there is still a significant gap between the SOP guidelines and the reality on the ground, such as delays in delivery and lack of responsiveness, which lead to a high number of guest complaints. Based on the evaluation of four performance dimensions (ability, discipline, responsibility, and cooperation), it was found that the level of discipline and responsibility of the bellboy is still low due to minimal supervision from superiors. Analysis using Herzberg’s Two-Factor Theory reveals that the root of this problem stems from the lack of maintenance of work facilities (hygiene factor) and minimal appreciation and self-development (motivator factor). This suboptimal performance has been proven to directly lower guest satisfaction levels and damage the hotel’s brand image in the eyes of the public. In conclusion, to achieve service excellence, hotel management must optimize the role of bellboys thru consistent supervision, improvement of work facilities, and continuous motivation and rewards to minimize guest complaints.